As potencialidades e desafios do uso do material dourado no ensino da matemática nos anos iniciais do ensino fundamental: uma revisão bibliográfica - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
This work sought to examine the possibilities and challenges of using golden material in teaching mathematics in the early years of Elementary School, through a bibliographic review. The objective is to analyze how the golden material can facilitate the understanding of abstract mathematical concepts, such as the decimal system and basic arithmetic operations, favoring more concrete and meaningful learning. The methodology adopted consists of reviewing relevant literature on the topic, in addition, scientific articles were surveyed on Google Scholar, as well as on Scielo and scientific journals, using as a reference the texts and contributions of authors such as Moura and Oliveira (2020 ) and Silveira (1998) who were fundamental in understanding the current and historical scenario of the use of concrete materials in mathematics education. The results indicate that the gold material has the potential to improve students’ logical reasoning and mathematical understanding by offering a visual and tactile representation of numerical concepts. However, significant challenges were identified, such as the need for adequate teacher training and sufficient educational resources in schools. It is concluded that, to overcome the challenges and maximize the possibilities offered by the golden material, na institutional commitment to the continuous training of teachers and alignment with curricular guidelines is essential. Thus, the material can be integrated effectively, contributing to more inclusive and effective mathematics teaching in the early years of Elementary School.
Keywords: Material Dourado; Desafios e possibilidades; Ensino da matemática; CNPQ:: CIÊNCIAS HUMANAS